Effectivity study of waste personal computer through manual dismantling and hydrometallurgical process using leaching process - Jaibee, Shafizan; Muhd Nor, Nik Hisyamudin; Azizul, Muhammad Redzuan; Abd Rahim, Abd Khalil; Mohammad, Fariza; Sia, Chee Kong; Ahmad, Md Fauzi; Seiji, Yokohama (Asian Research Publishing Network (ARPN), 2022)
Lately, the dumping of electrical and electronic at the market caused by the old electric and electronic goods has become outdated and often thrown away without any awareness of the dangers or about the precious material at goods. Generally the life of electrical and electronic waste (e-waste) just ended in landfills only. These items can be categorized as a valuable commodity and also a dangerous thing if we do not take steps that we should do about this stuff. Valuable materials contained in these products can be recycled, such as copper, aluminum, gold, steel, plastic and many more. However, the dangerous elements contained in the e-waste are chromium, beryllium, lead, mercury and so on. This study is focusing on the investigation of recycling potential of e-waste through manual dismantling process and leaching test. The methods that can be used for leaching are internal chamber and hydrometallurgical methods. These methods are used to obtain a solution containing precious and hazardous metals from the PCB. The leaching test was conducted with constant stirring speed, constant water-sample ratio and variable method. The liquid residue was analyzed by Atomic Absorption Spectroscopy (AAS). It was found that total time required to dismantle all parts in the waste motor is about 10 minutes and the part that required longest dismantling time was front cover. The metal elements that were observed are Zn, Cu, Mn, Pb and Cr. It was found that the pH of the solution increased with the increasing leaching time.